Gata3 hypermethylation and Foxp3 hypomethylation are associated with sustained protection and bystander effect following epicutaneous immunotherapy in peanut‐sensitized mice. Issue 1 (8th October 2018) - Mondoulet, L.; Dioszeghy, V.; Busato, F.; Plaquet, C.; Dhelft, V.; Bethune, K.; Leclere, L.; Daviaud, C.; Ligouis, M.; Sampson, H.; Dupont, C.; Tost, J.
Abstract: Background: Epicutaneous immunotherapy (EPIT) is a promising method for treating food allergies. In animal models, EPIT induces sustained unresponsiveness and prevents further sensitization mediated by Tregs. Here, we elucidate the mechanisms underlying the therapeutic effect of EPIT, by characterizing the kinetics of DNA methylation changes in sorted cells from spleen and blood and by evaluating its persistence and bystander effect compared to oral immunotherapy (OIT). Methods: BALB/c mice orally sensitized to peanut proteins (PPE) were treated by EPIT using a PPE‐patch or by PPE‐OIT. Another set of peanut‐sensitized mice treated by EPIT or OIT were sacrificed following a protocol of sensitization to OVA. DNA methylation was analyzed during immunotherapy and 8 weeks after the end of treatment in sorted cells from spleen and blood by pyrosequencing. Humoral and cellular responses were measured during and after immunotherapy. Results: Analyses showed a significant hypermethylation of the Gata3 promoter detectable only in Th2 cells for EPIT from the 4th week and a significant hypomethylation of the Foxp3 promoter in CD62L + Tregs, which was sustained only for EPIT. In addition, mice treated with EPIT were protected from subsequent sensitization and maintained the epigenetic signature characteristic for EPIT. Conclusions: Our study demonstrates that EPIT leads to a unique and stable epigenetic signature in specific T‐cell compartments with downregulation of Th2 key regulators and upregulation of Treg transcription factors, likely explaining the sustainability of protection and the observed bystander effect. Abstract : EPIT induces sustained hypermethylation of Gata 3 in Th2 cells and demethylation of Foxp3 in CD62L + Tregs. The epigenetic signature is unique compared to OIT. Gata3 hypermethylation and Foxp3 demethylation correlate with biologic effects, particularly the protection against further sensitizations.